Adolescent baseball pitchers with ulnar collateral ligament tears exhibit a high proportion of partial tears - Goodrich, E.; Cox, B.; Plummer, H. A.; Cohen, A.; Andrews, J. R.; Saper, M. (The American Journal of Sports Medicine, 2022)
Background: Ulnar collateral ligament (UCL) tears in the throwing elbow are classified according to grade and location using magnetic resonance arthrography (MRA). However, the frequency of each tear type and the association to age, competition level, and radiographic findings in adolescent baseball pitchers are unknown.